Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1186/1756-0500-6-289
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of condom use among clients at a Nigerian HIV Counseling and Testing Centre

Abstract: BackgroundStudies in Nigeria have shown that the main route of HIV transmission is sexual intercourse and that effective condom use protects people against infection. The objective of this study was to determine the pattern of condom use among clients of a friendly HIV Counseling and Testing (HCT) Centre in Osogbo southwestern Nigeria.MethodsThis was a review of the HCT Centre records from 2006 to 2010 retrieving socio-demographic information, sexual behaviour, condom use and result of HIV testing. Data obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 12 publications
1
10
2
Order By: Relevance
“…This is in contrast to a study conducted among Nigerian soldiers in Ilorin where condom use among respondents within the age range 18-34 years was reportedly low 21 . Another study conducted among clients visiting HCT center at Ogun state was at discordance with the finding of this study, where low use of condom among the younger clients was also reported 22 . A higher proportion of those who had never been in any marital union were recorded to have used a condom during their most recent sexual act compared to those who were married or living with a partner.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…This is in contrast to a study conducted among Nigerian soldiers in Ilorin where condom use among respondents within the age range 18-34 years was reportedly low 21 . Another study conducted among clients visiting HCT center at Ogun state was at discordance with the finding of this study, where low use of condom among the younger clients was also reported 22 . A higher proportion of those who had never been in any marital union were recorded to have used a condom during their most recent sexual act compared to those who were married or living with a partner.…”
Section: Discussioncontrasting
confidence: 92%
“…Level of education has been identified as a determinant of increased condom use in non-marital relationship 25 . On the contrary, higher level of education was found to be related to non-use of condoms during the most recent act of sexual intercourse in a particular study 22 . Condom use during last sex was increased among the richer wealth index in this study was corroborated by findings from other studies in Ibadan and also Lusaka which reported that condom use increased with improved socio economic status 26,27 .…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…HIV/AIDS stigma commonly occurs as the disease is perceived as being contracted only through extramarital sex. Hence, HIV positive patients experience stigma from close family members, colleagues in places of work, schools and religious gatherings where many still recognize the virus as “a curse” and HIV positive people as “sinners” [ 15 - 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is commendable since consistent and correct use of condom has been widely recommended as a public health strategy against sexually transmitted infections, including heterosexual transmission of HIV infection [14]. This finding is in contrast to the study done in Osun State, Nigeria which shows a higher prevalence among married respondents [15]. Desire for children could have prevented the married from using condom [16, 17].…”
Section: Discussionmentioning
confidence: 99%